Comparative analysis of database access technology - Barczak, Andrzej; Zacharczuk, Dariusz; Jastrzębowski, Stanisław (Studia Informatica. System and information technology, 2009)
The paper’s subject is comparative analysis of database access technologies. It presents the evolution of the discussed technologies, which are divided into the following categories: single-platform and multi-platform technologies. Sample programs showing the use of programming interfaces, used for initiating and establishing connections with databases and performing simple operations on them. A database diagram, which was used for measuring efficiency of selected technologies as well as testing plan and concept, system and hardware parameters, tested queries and the program skeleton that was used for measuring the efficiency of selected technologies, were presented. The results were grouped according to 4 query types and 3 operating systems. A description was attached to each graph. Conclusions were provided for query tests for each of the operating systems. Finally, the most efficient technologies were discussed, potential causes of increase or decrease in efficiency were presented, and the results were summarized.